Eine andere historische Subjektivierung: Überlegungen mit Jacques Rancière, Walter Benjamin und John Milbank - Lehmann, Sandra (Österreichische Zeitschrift für Geschichtswissenschaften, 2016)
In focusing on Jacques Rancière and Walter Benjamin, the main concern of this essay is to outline an alternative concept of the historical subject. As I assume, subjectivity primarily forms itself in being oriented to that which is incommensurable, namely, the radical positivity of being itself. First, I show that Rancière’s concept of ‘equality’ can be read in terms of this basic formative movement. Equality enables political claims and, accordingly, political subjecti cation while, ultimately, remaining irredeemable. Yet, I do not agree with the aporetic character of equality in Rancière, which, in my view, creates a perpetuation of injustice. In order to overcome it, I draw on Benjamin and demonstrate that, in implicitly referring to redemption, the irredeemable has a positive content. In a relative way, it can be restored when ever the remembrance of past suffering is incorporated into new claims of justice. Historical subjects originate in this merging of present and past.